(untitled) (Research, Society and Development, 2020)
Objectives: To analyze fetal deaths, according to their socio-demographic, clinical characteristics and avoidability criteria, which occurred in a reference maternity hospital. Methods: Retrospective study of cases of fetal deaths that occurred in a maternity reference for high risk, from 2014 to 2017. A spreadsheet was prepared in Excel 2010, with all the variables contained in the fetal death investigation form. Descriptive analyzes were carried out and the causes of deaths were classified, according to the preventability criterion, by weight range (1500g-2500g;> 2500g). Results: There were 1029 deaths in the studied period. The fetal mortality rate varied from 25.1 / 1000 live births in 2013 to 26.1 / 1000 live births in 2017. As for maternal age, 39.9% were between 20 and 40 years old; 39.9% had more than 8 years of study. The most cited pathologies / risk factors during pregnancy were: arterial hypertension / DHEG (33.1%), hemorrhage / PPD / placenta previa (31.1%) and urinary tract infection (20.1%). Regarding the mother’s condition, at the time of hospitalization, 38.4% had premature amniorrexis without labor, 9.7% had severe pre-eclampsia and 9.1% had placental abruption. The complications during childbirth that stood out were eclampsia / hypertension (25.6%), hemorrhage (20.2%). Of the 570 fetal deaths (over 1500g) analyzed according to the preventability criterion, 84.9% occurred from preventable causes, 4.9% from causes that are not clearly avoidable and 10.2% from ill-defined causes. The main causes of preventable fetal deaths (n = 484) studied were classified as: reducible by adequate care for women during pregnancy (56.6%) and adequate care for women during childbirth (36.4%) and adequate care for newborns born (7.0%). Conclusion:The findings reveal a high proportion of fetal deaths that could be avoided with actions aimed at improving the quality of prenatal and childbirth care.